Blood Immune Cell Composition Associated with Obesity and Drug Repositioning Revealed by Epigenetic and Transcriptomic Conjoint Analysis - Liu, Jia-Chen; Liu, Sheng-Hua; Fu, Guang; Qiu, Xiao-Rui; Jiang, Run-Dong; Huang, Sheng-Yuan; Zhu, Li-Yong; Li, Wei-Zheng (Frontiers in Pharmacology, 2021)
This research was designed to analyze the composition of immune cells in obesity and identify novel and potent drugs for obesity management by integrating the epigenome and transcriptome data. DNA methylation data set (GSE166611) and microRNA (miRNA) and mRNA expression microarray (GSE53377 and GSE18897) were obtained from the GEO database. A total of 144 individuals (91 obese samples and 53 controls) were included in the study. Differential expression analysis and immune cell composition analysis were accomplished using R (version 4.0.4). Functional and enrichment analysis was performed using FunRich software (http://www.funrich.org). The protein-protein interaction (PPI) network was constructed by STRING and visualized in Cytoscape (version 3.8.2). Finally, drug repositioning by connectivity map (CMap) analysis was performed to screen potential therapeutic agents for obesity. A total of 318 DEGs were identified in this study (149 upregulated and 169 down-regulated). Enrichment analysis showed that differential genes (including gene targets for methylation and miRNA targets) were enriched mainly in apoptosis, inflammation, and immune-related pathway. Immune cell composition analysis found that resting memory CD4(+) T cells, monocytes, M0 and M2 macrophages may be relevant to the obesity process. Five chemicals, including iloprost, securinine, torin-1, tamoxifen, sirolimus were identified as putative therapeutic agents of obesity.